MODELO DE ALGORITMO PARA A GESTÃO ADEQUADA DOS RESÍDUOS DA CONSTRUÇÃO CIVIL POR AGENTES PÚBLICOS E PRIVADOS - Gonçalves, Sandra Cunha; Fornari, Celso Carlino (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704795 The Construction Industry as a generator of waste, have an important role in shaping the future,from the moment that embodies the culture of responsibility to preserve the environment. Even ifproperly manage the waste is still a problem faced by society in recent years to see changes in theconstruction industry, by introducing new technologies into their construction processes. Whetherthe methods and techniques of rationalization, sorting and recycling of waste through therecycling process and, when responsibility for the final destination of the waste generated at theconstruction site. This study aims to outline a model that sequencie the main activities to beadopted by public and private agencies, to enable them to manage their waste in accordance withspecific legislation.